Trends, patterns and determinants of biodiversity conservation outcomes in Buxa Tiger Reserve, West Bengal, India. Issue 1 (3rd April 2023) - Das, Uttam; Behera, Bhagirath
ABSTRACT: This paper analyses the trends, patterns and determinants of biodiversity conservation in the Buxa Tiger Reserve (BTR), India. Temporal remote sensing data from 1990 to 2020 shows a loss of 27.69 km2. The results show that the total forest area has seen a significant decline from 1990 to 2020, whereas non-forest and degraded forest areas have been on the rise. The decline of forest area is observed more in fringe and lower altitude areas where accessibility is easy for humans to extract forest resources. The secondary data shows a decline in the wildlife population including the flagship species, the Bengal tiger. The decline in natural resources due to human activities in the BTR is likely to continue unless a participatory biodiversity conservation programme is established. The establishment of the Joint Forest Management Committee (JFMC), a formal local institution where local communities and forest departments (FDs) jointly share the rights and responsibility towards the use and management of the forest, seems to be effective in reducing negative forest activities. The sustainability of the BTR is possible if the local people abandon the 'tragedy of the commons' activities and work together, with government guidance for the promotion of livelihoods and biodiversity conservation.